Vector Competence of Culex neavei (Diptera: Culicidae) for Usutu Virus - Nikolay, Birgit (The American Society of Tropical Medicine and Hygiene, 2012)
Usutu virus (USUV), a flavivirus belonging to the Japanese encephalitis serocomplex, was isolated for the first time from a Culex neavei mosquito in 1959 in South Africa. Despite multiple isolations of USUV from Cx. neavei in Africa, its vector competence remains unproven. Therefore, we infected Cx. neavei orally with the USUV reference strain and used reverse transcription–polymerase chain reaction and an indirect immunofluorescence assay to detect virus in bodies, legs, wings, and saliva of mosquitoes. We demonstrated the susceptibility of Cx. neavei mosquitoes for the USUV reference strain, its potential to be transmitted, and infection, dissemination, and transmission rates of 90.9%, 40.0%, and 81.3%, respectively. Also, we showed that infection rates are dependent on the virus titer of the blood meal. Given the bionomics of Cx. neavei, its role as enzootic vector for USUV in Africa in a mosquito-bird transmission cycle or as bridge vector for USUV transmission to humans is discussed.